2007
DOI: 10.1016/j.tsf.2006.12.179
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of erbium implanted tungsten oxide films deposited by reactive dual magnetron sputtering

Abstract: Amorphous and partially crystalline WO 3 thin films were prepared by reactive dual magnetron sputtering and successively implanted by erbium ions with a fluence in the range from 7.7 × 10 14 to 5 × 10 15 ions/cm 2 . The electrical and optical properties were studied as a function of the film deposition parameters and the ion fluence. Ion implantation caused a strong decrease of the resistivity, a moderate decrease of the index of refraction and a moderate increase of the extinction coefficient in the visible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
(27 reference statements)
2
7
0
Order By: Relevance
“…Thus, the observed amorphization at higher plasma processing powers is related to the surface chemistry changes and to the ion bombardment effects. This effect is similar to that of ion implantation at low temperature [25].…”
Section: Structural Properties 311 Film Composition and Thicknesssupporting
confidence: 78%
“…Thus, the observed amorphization at higher plasma processing powers is related to the surface chemistry changes and to the ion bombardment effects. This effect is similar to that of ion implantation at low temperature [25].…”
Section: Structural Properties 311 Film Composition and Thicknesssupporting
confidence: 78%
“…Thus, the observed amorphization at higher plasma powers or times is related to the thickness reduction, the surface chemistry changes and to the ion bombardment effects. This effect is similar to that of ion implantation at low temperature [49].…”
Section: Film Temperature Thickness Composition and Structuresupporting
confidence: 78%
“…The experimentally determined values of n are in close agreement with the earlier reported values for WO 3 . 43 It is noted that the refractive index, n increases with Pd incorporation concentration. concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Tungsten oxide is highly insulating as long as the material is stoichiometric. The reported values of resistivity of physical vapor deposited tungsten oxide films lie in the range of 10 1 -10 6 m. [44][45][46][47] Delamare et al, 48 have reported a low resistivity of 5 6 × 10 −3 m for the WO 3 nanorods grown on mica substrates. In the present study the resistivity values of the investigated films lie between 0.602 m to 17 m. The slight increase in resistivity observed for the 5 wt% Pd incorporated WO 3 film compared to that of 1 wt% Pd incorporated WO 3 film can be due to the grain boundary scattering induced by the incorporated Pd segregation as suggested from the Raman spectral data.…”
Section: Resultsmentioning
confidence: 99%